Perencanaan Dan Rekrutmen SDM Di KFC - Wirda Annisa; Hendra Riofita (Lembaga Pengembangan Kinerja Dosen, 2024)
Human resource planning and recruitment at KFC are crucial elements in supporting the company’s growth and operational sustainability. This article explores the strategies employed by KFC to forecast human resource needs and the recruitment processes that ensure optimal placement of employees. KFC leverages technology and digital platforms to streamline the recruitment process, emphasizing training and development as part of its long-term strategy. As a result, the company not only meets its human resource requirements but also enhances employee loyalty and motivation. This article provides insights for other companies on the importance of integrating strategic and innovative human resource planning.